THE DISTRIBUTION OF WAGES, JOBS, CO-WORKERS, AND SUPERVISION TO WORKERS’ JOB SATISFACTION - Dewi Untari; Muhammad Irsyad Raspati; Sari Sri Handani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The goal of this research is to find out the distribution of wages, jobs, co-workers, and supervision to the workers’s job satisfaction, both partially and simultaneously. The methods used in this research are descriptive and verificative, using questionnaire. The research shows: The distribution of wages is categorized as good with ttotal score of 365, jobs are also categorized as good, scored 546, co-workers is categorized as good, scored 435, supervision is categorized as good with the score of 353, and job satisfaction is categorized as good scored 309. Partially, wages has positive effect and significant toward workers’s job satisfaction, where as thitung > ttabel of 3.492 > 2.365. Jobs is proven to have positif and significant effect on workers’s job satifaction, where as thitung > ttabel of 5.255 > 2.365. Co-workers was proven to have positive but not significant effect on workers’s job satisfaction, where as thitung > ttabel of 2.047 > 2.365. Supervision was proven to have negative and significant effect on workers’s job satisfaction, where as thitung > ttabel of -3.130 > -2.365. Simultaneously, there was proven that there were positive effects of wages, jobs, co-workers, and supervision to workers’s job satisfaction, where as of Fhitung > Ftabel 23.053 > 4.12. Based on the result of the hypothesis, it was concluded that effect amongst wages, jobs, co-workers, and supervision, to workers’s job satisfaction, both partially and simultaneously.